Re-Writing “Pleasure and Necessity”: The Female Reader of Hegel’s Phenomenology of Spirit - Feeney, Amanda Lynn (Université d'Ottawa / University of Ottawa, 2016)
This thesis demonstrates that “Pleasure and Necessity”, a section of Hegel’s Phenomenology of Spirit, both should and can be re-written, bringing the female reader out of the margins and into the texts of Hegel’s Absolute system. First, I demonstrate that the Phenomenology is a Bildungsroman that is both important for the reader’s philosophical education and Hegelian science itself. I provide an interpretation of “Pleasure and Necessity”, demonstrate that this section alienates the female reader, and discuss why Antigone is not a solution to this problem. Rather, I conclude that this stage should be re-written. Furthermore, I argue that “Pleasure and Necessity” can be re- written because the Phenomenology already contains the outline of its own re-writing insofar as it corresponds to the Logic. Finally, I re-write “Pleasure and Necessity” as “Impulse and Ought”, using new figures to re-stage the logical operation that occurs in the original text.
Keywords: Hegel; Feminist Philosophy; Phenomenology of Spirit